Nano thermal radiation warm-keeping composite fabric and manufacturing method thereof

By using a composite fabric filled with nano-thermal radiation particles and nano-insulating particles with a germanium shell in the heat-radiating fabric, the existing heat-radiating fabric has solved the problems of low far-infrared emissivity and poor insulation effect, achieving efficient far-infrared radiation and significant insulation effect.

CN119590055AActive Publication Date: 2025-03-11GAOFAN (ZHEJIANG) INFORMATION TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411025725.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2025-03-11
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

The existing thermally radiant fabrics have low far infrared emissivity, poor heating effect, and poor insulation effect.

Method used

The composite fabric that is heat-conserving with nano-thermal radiation is used, including a heat-radiating fiber layer and a thermally insulated fiber layer. The textile raw material of the thermally radiating fiber layer is the matrix fiber filled with germanium shell and semi-covered tourmaline structure nano-thermal radiation particles, and the textile raw material of the thermally insulated fiber layer is hollow polyester fiber filled with nano-insulated particles.

Benefits of technology

It improves the far infrared emissivity and heating effect of the fabric, while significantly improving the insulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004968473400000081
    Figure BDA0004968473400000081
  • Figure BDA0004968473400000091
    Figure BDA0004968473400000091
Patent Text Reader

Abstract

The invention discloses a nano thermal radiation warmth retention composite fabric and a manufacturing method thereof.The composite fabric comprises a thermal radiation fiber layer serving as an inner layer material and a heat preservation fiber layer serving as a surface layer material, and the textile raw material of the thermal radiation fiber layer is matrix fibers filled with nano thermal radiation particles; the nanometer thermal radiation particles are of a germanium shell semi-coated tourmaline structure, and the textile raw material of the heat preservation fiber layer is hollow polyester fibers filled with nanometer heat preservation particles. According to the invention, a germanium shell semi-coated tourmaline structure is adopted as a nano thermal radiation particle, so that the far infrared properties of germanium and tourmaline are doubly superposed and complemented with each other, meanwhile, the dispersion effect of the particles in the fiber can be improved, the layering or agglomeration of the particles is avoided, and finally, the overall far infrared ray emissivity of the fabric is high, and the heating effect is good. The composite fabric further comprises a heat preservation fiber layer made of hollow polyester fibers filled with nanometer heat preservation particles, so that the overall heat preservation effect of the fabric is outstanding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of clothing fabric preparation, and in particular to a nano thermal radiation warmth-keeping composite fabric and a preparation method thereof. Background Art

[0002] Far infrared fiber is a typical material for heating and heat storage. Due to the addition of far infrared additives during the spinning process, it can absorb external heat and store it for radiation to the human body, while reflecting the far infrared radiation radiated outward by the human body, thereby playing a role in heating. At the same time, when the far infrared radiation is absorbed by the human body, it can also promote physical health to a certain extent. Therefore, the application of far infrared fiber to process into thermal radiation function of thermal clothing fabrics has been widely studied and applied in recent years, especially for down fabric products, which can reduce the amount of down filling while maintaining the warmth effect, thereby achieving lightweight clothing.

[0003] However, most of the far-infrared additives used in existing heat-radiating fabrics are single substances, or multiple substances are directly mixed, such as one or more of tourmaline, medical stone, far-infrared ceramic powder, germanium stone, and potassium feldspar. These far-infrared additives lack mutual synergy, resulting in a low far-infrared emissivity of the entire fabric and a poor warming effect. In addition, most of the existing heat-radiating fabrics use a single fiber layer, resulting in poor thermal insulation effect. Summary of the invention

[0004] The object of the present invention is to provide a nano thermal radiation warm-keeping composite fabric and a manufacturing method thereof, which solves the problems of low far-infrared emissivity, poor heating and heat preservation effects of existing thermal radiation fabrics.

[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0006] A nano thermal radiation warmth-keeping composite fabric, the composite fabric comprising a thermal radiation fiber layer as an inner layer material and a thermal insulation fiber layer as a surface layer material, wherein the textile raw material of the thermal radiation fiber layer is a matrix fiber filled with nano thermal radiation particles, and the nano thermal radiation particles adopt a germanium shell semi-covered tourmaline structure, and the textile raw material of the thermal insulation fiber layer is a hollow polyester fiber filled with nano thermal insulation particles.

[0007] A further improvement is that the matrix fiber is selected from one of polyester fiber, polyamide fiber, acrylic fiber, polypropylene fiber or spandex fiber.

[0008] A further improvement is that the nano thermal insulation particles are nano silicon dioxide aerogel particles or nano polyurethane aerogel particles.

[0009] The present invention also provides a method for preparing a nano thermal radiation warmth-keeping composite fabric, the steps comprising:

[0010] S1. Using nano-germanium dioxide powder and nano-tourmaline powder as raw materials, preparing nano-thermal radiation particles with a germanium shell and a semi-covered tourmaline structure;

[0011] S2, placing nano thermal radiation particles in an organic solvent, adding a dispersant, stirring and dispersing to obtain a thermal radiation slurry, mixing the thermal radiation slurry with matrix fiber slices, drying and melt granulating to obtain a thermal radiation masterbatch, melt spinning the thermal radiation masterbatch, and then thermally stretching, relaxing and heat-setting to obtain a thermal radiation fiber, and finally spinning the thermal radiation fiber to obtain a thermal radiation fiber layer;

[0012] S3, taking nano thermal insulation particles as an online added component, taking polyester melt as the main melt, and setting the spinneret hole as a hollow structure, performing online addition melt spinning, and then obtaining hollow polyester fibers through heat stretching, relaxation and heat setting, and finally weaving the hollow polyester fibers to obtain a thermal insulation fiber layer;

[0013] S4, bonding the heat radiation fiber layer and the thermal insulation fiber layer to obtain the nano heat radiation warmth-keeping composite fabric.

[0014] The further improvement lies in that the specific process of step S1 is as follows: dissolving nano-germanium dioxide powder in a sodium hydroxide solution and adjusting the pH of the solution to 6-8 to obtain solution A; dispersing nano-tourmaline powder in a polyvinyl pyrrolidone solution and stirring for 6-12 hours to obtain solution B; mixing solution A and solution B evenly, adding a sodium borohydride solution to the mixed solution, heating to 80-100° C. and reacting for 10-14 hours; filtering the obtained product to obtain a filter residue; washing and drying the filter residue, and then sintering at 750-850° C. for 6-8 hours to obtain nano-thermal radiation particles with a tourmaline structure fully covered by a germanium shell; taking the nano-thermal radiation particles, removing part of the germanium shell on the surface of the particles by dry etching technology, and obtaining nano-thermal radiation particles with a tourmaline structure half covered by a germanium shell.

[0015] The further improvement lies in that the concentration of the sodium hydroxide solution is 10-14 mol / L, and the dosage ratio of the nano-germanium dioxide powder to the sodium hydroxide solution is 1 g:50-100 mL, the concentration of the polyvinyl pyrrolidone solution is 0.02-0.05 mg / mL, and the dosage ratio of the nano-tourmaline powder to the polyvinyl pyrrolidone solution is 1 g:20-50 mL, the mass ratio of the solution A to the solution B is 1:4-6, the concentration of the sodium borohydride solution is 0.1-0.3 g / mL, and the mass ratio of the sodium borohydride solution to the mixed solution is 1:3-4.

[0016] A further improvement is that the etching gases used in the dry etching are chlorine and oxygen, wherein the chlorine flow rate is 100-200sccm, the oxygen flow rate is 5-50sccm, the etching pressure is 50-200mtorr, the source power is 600-700W, the bias power is 120-150W, and the etching time is 3-5min.

[0017] A further improvement is that in step S2, the mass ratio of the nano thermal radiation particles, the organic solvent and the dispersant is 1:1.5-3:0.05-0.1, the mass ratio of the thermal radiation slurry to the matrix fiber slice is 1:3-8, and the organic solvent is one of ethanol, ethylene glycol or isopropanol, and the dispersant is one of polyvinyl pyrrolidone, sebacic acid, trimethylolethane, polyethylene glycol ester or phenyl benzoate.

[0018] A further improvement is that in step S2, the melt spinning temperature is 250-280°C, the speed is 800-1500 m / min, the spinneret diameter is 0.25-0.4 mm, the stretching ratio during stretching is 3.2-3.5, and the temperature during relaxation heat setting is 65-80°C.

[0019] Further improvement lies in that in step S3, the mass ratio of nano thermal insulation particles to polyester melt is 8-15%, the melt spinning temperature is 280-300°C, the speed is 1000-1400m / min, the spinneret hole cross-section is annular, and the outer diameter is 0.6mm, the inner diameter is 0.4mm, the stretching ratio during stretching is 3.0-3.4, and the temperature during relaxation heat setting is 80-100°C.

[0020] The beneficial effects of the present invention are as follows: (1) The present invention adopts a germanium shell semi-covered tourmaline structure as a nano thermal radiation particle, so that the far-infrared performance of germanium and tourmaline is doubled and complements each other, and at the same time, the dispersion effect of the particles in the fiber is improved, and the particle stratification or agglomeration is avoided, and finally the overall far-infrared emissivity of the fabric is high and the warming effect is good. (2) The composite fabric of the present invention also includes a thermal insulation fiber layer made of hollow polyester fibers filled with nano thermal insulation particles, so that the overall thermal insulation effect of the fabric is outstanding. DETAILED DESCRIPTION

[0021] The present application is further described in detail below in conjunction with specific embodiments. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technical personnel in this field can make some non-essential improvements and adjustments to the present application based on the above application content.

[0022] 1. Main Materials

[0023] (1) Nano-germanium dioxide powder: purchased from Qinghe Yaoxie Metal Materials Co., Ltd., with a particle size of 20-50 nm and a purity greater than 99.9%.

[0024] (2) Nano-tourmaline powder: purchased from Shijiazhuang Chenghe New Material Technology Co., Ltd., with a particle size of 400-500 nm and a density of 3.15 g / cm 3 .

[0025] (3) Nano-silica aerogel particles: purchased from Shandong Jiquan Biotechnology Co., Ltd., with a particle size of 200-240 nm.

[0026] (4) Nano-polyurethane aerogel particles: First, 100 g of diphenylmethane diisocyanate acetone solution and 350 g of propylene glycol polyether acetone solution were mixed evenly, and then 0.8 g of dibutyltin dilaurate was added. The mixture was allowed to stand for 12 h to obtain a gel. The gel was then washed with acetone for three times and supercritically dried to obtain nano-polyurethane aerogel particles with a particle size of 200-280 nm.

[0027] 2. Implementation of the experiment

[0028] Example 1

[0029] A nano thermal radiation warmth-keeping composite fabric, the composite fabric comprising a thermal radiation fiber layer as an inner layer material and a thermal insulation fiber layer as a surface layer material, wherein the textile raw material of the thermal radiation fiber layer is polyester fiber filled with nano thermal radiation particles, and the nano thermal radiation particles adopt a germanium shell semi-covered tourmaline structure, and the textile raw material of the thermal insulation fiber layer is hollow polyester fiber filled with nano thermal insulation particles, and the nano thermal insulation particles adopt nano silica aerogel particles.

[0030] The preparation steps of the composite fabric are as follows:

[0031] S1. Dissolve nano-germanium dioxide powder in a sodium hydroxide solution with a concentration of 10 mol / L at a dosage ratio of 1 g:50 mL, and adjust the solution pH to 6 to obtain solution A; disperse nano-tourmaline powder in a polyvinyl pyrrolidone solution with a concentration of 0.02 mg / mL at a dosage ratio of 1 g:20 mL, and stir for 6 h to obtain solution B; mix solution A and solution B at a mass ratio of 1:4, add sodium borohydride solution with a concentration of 0.1 g / mL to the mixed solution, and the mass ratio of the sodium borohydride solution to the mixed solution is 1:3, and heat to 80°C for reaction. 14h, filter the resulting product to obtain a filter residue, wash and dry the filter residue, and then sinter at 750°C for 8h to obtain nano thermal radiation particles with a germanium shell fully covering a tourmaline structure, take the nano thermal radiation particles, and use dry etching technology to remove part of the germanium shell on the surface of the particles to obtain nano thermal radiation particles with a germanium shell half-covered tourmaline structure; the etching gases used in the dry etching are chlorine and oxygen, wherein the chlorine flow rate is 100sccm, the oxygen flow rate is 5sccm, the etching pressure is 50mtorr, the source power is 600W, the bias power is 120W, and the etching time is 5min.

[0032] S2, taking nano thermal radiation particles and placing them in an organic solvent, adding a dispersant, and obtaining a thermal radiation slurry by stirring and dispersing, taking the thermal radiation slurry and mixing it with polyester fiber slices, and then melting and granulating it after drying to obtain a thermal radiation masterbatch, and taking the thermal radiation masterbatch for melt spinning, the melt spinning temperature is 250°C, the speed is 800m / min, the spinneret hole diameter is 0.25mm, and then thermal stretching, relaxation and heat setting are performed to obtain thermal radiation fibers, the stretching ratio during stretching is 3.2, and the temperature during relaxation and heat setting is 65°C; finally, the thermal radiation fibers are woven to obtain a thermal radiation fiber layer; wherein the mass ratio of the nano thermal radiation particles, the organic solvent and the dispersant is 1:1.5:0.05, the mass ratio of the thermal radiation slurry to the polyester fiber slices is 1:3, and the organic solvent is ethanol, and the dispersant is polyvinyl pyrrolidone.

[0033] S3, taking nano thermal insulation particles as an online added component, with polyester melt as the main melt, the mass ratio of nano thermal insulation particles to polyester melt is 8%, and the spinneret hole is set as a hollow structure, and online addition melt spinning is carried out, the melt spinning temperature is 280°C, the speed is 1000m / min, the spinneret hole cross-section is annular, and the outer diameter is 0.6mm, the inner diameter is 0.4mm, and then the hollow polyester fiber is obtained by heat stretching and relaxation heat setting, the stretching ratio during stretching is 3.0, and the temperature during relaxation heat setting is 80°C; finally, the hollow polyester fiber is woven to obtain a thermal insulation fiber layer.

[0034] S4, bonding the heat radiation fiber layer and the thermal insulation fiber layer to obtain the nano heat radiation warmth-keeping composite fabric.

[0035] Example 2

[0036] A nano thermal radiation warmth-keeping composite fabric, the composite fabric comprising a thermal radiation fiber layer as an inner layer material and a thermal insulation fiber layer as a surface layer material, wherein the textile raw material of the thermal radiation fiber layer is polyamide fiber filled with nano thermal radiation particles, and the nano thermal radiation particles adopt a germanium shell semi-covered tourmaline structure, and the textile raw material of the thermal insulation fiber layer is hollow polyester fiber filled with nano thermal insulation particles, and the nano thermal insulation particles adopt nano silica aerogel particles.

[0037] The preparation steps of the composite fabric are as follows:

[0038] S1. Dissolve nano-germanium dioxide powder in a sodium hydroxide solution with a concentration of 12 mol / L at a dosage ratio of 1 g:80 mL, and adjust the solution pH to 7 to obtain solution A; disperse nano-tourmaline powder in a polyvinyl pyrrolidone solution with a concentration of 0.03 mg / mL at a dosage ratio of 1 g:35 mL, and stir for 9 h to obtain solution B; mix solution A and solution B at a mass ratio of 1:5, add sodium borohydride solution with a concentration of 0.2 g / mL to the mixed solution, and the mass ratio of the sodium borohydride solution to the mixed solution is 1:3.5, and heat to 90°C for reaction. 12h, filter the resulting product to obtain a filter residue, wash and dry the filter residue, and then sinter at 800°C for 7h to obtain nano thermal radiation particles with a germanium shell fully coated with a tourmaline structure, take the nano thermal radiation particles, and use dry etching technology to remove part of the germanium shell on the surface of the particles to obtain nano thermal radiation particles with a germanium shell half coated with a tourmaline structure; the etching gases used in the dry etching are chlorine and oxygen, wherein the chlorine flow rate is 150sccm, the oxygen flow rate is 25sccm, the etching pressure is 100mtorr, the source power is 650W, the bias power is 135W, and the etching time is 4min.

[0039] S2, taking nano thermal radiation particles and placing them in an organic solvent, adding a dispersant, and obtaining a thermal radiation slurry by stirring and dispersing, taking the thermal radiation slurry and mixing it evenly with polyamide fiber slices, drying and melt granulating to obtain thermal radiation masterbatch, taking the thermal radiation masterbatch for melt spinning, the melt spinning temperature is 260°C, the speed is 1100m / min, the spinneret hole diameter is 0.35mm, and then thermal stretching, relaxation and heat setting are performed to obtain thermal radiation fibers, the stretching ratio during stretching is 3.3, and the temperature during relaxation and heat setting is 70°C; finally, the thermal radiation fibers are woven to obtain a thermal radiation fiber layer; wherein the mass ratio of the nano thermal radiation particles, the organic solvent and the dispersant is 1:2:0.08, the mass ratio of the thermal radiation slurry to the polyamide fiber slices is 1:5, and the organic solvent is ethylene glycol, and the dispersant is sebacic acid.

[0040] S3. Nano thermal insulation particles are taken as online added components, polyester melt is used as the main melt, the mass ratio of nano thermal insulation particles to polyester melt is 12%, and the spinneret hole is set as a hollow structure, and online melt spinning is performed. The melt spinning temperature is 290°C, the speed is 1200m / min, the cross-section of the spinneret hole is annular, and the outer diameter is 0.6mm, and the inner diameter is 0.4mm. Then, hollow polyester fibers are obtained by heat stretching and relaxation heat setting. The stretching ratio during stretching is 3.2, and the temperature during relaxation heat setting is 90°C; finally, the hollow polyester fibers are woven to obtain a thermal insulation fiber layer.

[0041] S4, bonding the heat radiation fiber layer and the thermal insulation fiber layer to obtain the nano heat radiation warmth-keeping composite fabric.

[0042] Example 3

[0043] A nano thermal radiation warmth-keeping composite fabric, the composite fabric comprising a thermal radiation fiber layer as an inner layer material and a thermal insulation fiber layer as a surface layer material, wherein the textile raw material of the thermal radiation fiber layer is polypropylene fiber filled with nano thermal radiation particles, and the nano thermal radiation particles adopt a germanium shell semi-covered tourmaline structure, and the textile raw material of the thermal insulation fiber layer is hollow polyester fiber filled with nano thermal insulation particles, and the nano thermal insulation particles adopt nano polyurethane aerogel particles.

[0044] The preparation steps of the composite fabric are as follows:

[0045] S1. Dissolve nano-germanium dioxide powder in a sodium hydroxide solution with a concentration of 14 mol / L at a dosage ratio of 1 g:100 mL, and adjust the solution pH to 8 to obtain solution A; disperse nano-tourmaline powder in a polyvinyl pyrrolidone solution with a concentration of 0.05 mg / mL at a dosage ratio of 1 g:50 mL, and stir for 12 h to obtain solution B; mix solution A and solution B at a mass ratio of 1:6, add sodium borohydride solution with a concentration of 0.3 g / mL to the mixed solution, and the mass ratio of the sodium borohydride solution to the mixed solution is 1:4, and heat to 100 ° C and react. The reaction mixture was sintered for 10 hours, the product was filtered to obtain a filter residue, the filter residue was first washed and dried, and then sintered at 850° C. for 6 hours to obtain nano thermal radiation particles with a germanium shell fully covering a tourmaline structure, the nano thermal radiation particles were taken, and a part of the germanium shell on the surface of the particles was removed by dry etching technology to obtain nano thermal radiation particles with a germanium shell half-covered tourmaline structure; the etching gases used in the dry etching were chlorine and oxygen, wherein the chlorine flow rate was 200 sccm, the oxygen flow rate was 50 sccm, the etching pressure was 200 mtorr, the source power was 700 W, the bias power was 150 W, and the etching time was 3 min.

[0046] S2, taking nano thermal radiation particles and placing them in an organic solvent, adding a dispersant, and obtaining a thermal radiation slurry by stirring and dispersing, taking the thermal radiation slurry and mixing it evenly with polypropylene fiber slices, drying and melt granulating to obtain a thermal radiation masterbatch, taking the thermal radiation masterbatch for melt spinning, the melt spinning temperature is 280°C, the speed is 1500m / min, the spinneret hole diameter is 0.4mm, and then thermal stretching, relaxation and heat setting are performed to obtain thermal radiation fibers, the stretching ratio during stretching is 3.5, and the temperature during relaxation and heat setting is 80°C; finally, the thermal radiation fibers are woven to obtain a thermal radiation fiber layer; wherein the mass ratio of the nano thermal radiation particles, the organic solvent and the dispersant is 1:3:0.1, the mass ratio of the thermal radiation slurry to the polypropylene fiber slices is 1:8, and the organic solvent is isopropanol, and the dispersant is polyethylene glycol ester.

[0047] S3. Take nano thermal insulation particles as online added components, use polyester melt as the main melt, the mass ratio of nano thermal insulation particles to polyester melt is 15%, and set the spinneret hole as a hollow structure, and perform online added melt spinning. The melt spinning temperature is 300°C, the speed is 1400m / min, the spinneret hole cross-section is annular, and the outer diameter is 0.6mm, the inner diameter is 0.4mm, and then the hollow polyester fiber is obtained by heat stretching and relaxation heat setting. The stretching ratio during stretching is 3.4, and the temperature during relaxation heat setting is 00°C; finally, the hollow polyester fiber is woven to obtain a thermal insulation fiber layer.

[0048] S4, bonding the heat radiation fiber layer and the thermal insulation fiber layer to obtain the nano heat radiation warmth-keeping composite fabric.

[0049] Comparative Example 1

[0050] A nano thermal radiation warmth-keeping composite fabric, the composite fabric comprising a thermal radiation fiber layer as an inner layer material and a thermal insulation fiber layer as a surface layer material, wherein the textile raw material of the thermal radiation fiber layer is polyamide fiber filled with nano thermal radiation particles, and the nano thermal radiation particles adopt a tourmaline structure fully covered with a germanium shell, and the textile raw material of the thermal insulation fiber layer is hollow polyester fiber filled with nano thermal insulation particles, and the nano thermal insulation particles adopt nano silica aerogel particles.

[0051] The preparation steps of the composite fabric are as follows:

[0052] S1. Dissolve nano-germanium dioxide powder in a sodium hydroxide solution with a concentration of 12 mol / L at a dosage ratio of 1 g:80 mL, and adjust the solution pH to 7 to obtain solution A; disperse nano-tourmaline powder in a polyvinyl pyrrolidone solution with a concentration of 0.03 mg / mL at a dosage ratio of 1 g:35 mL, and stir for 9 hours to obtain solution B; mix solution A and solution B evenly at a mass ratio of 1:5, add sodium borohydride solution with a concentration of 0.2 g / mL to the mixed solution, and the mass ratio of the sodium borohydride solution to the mixed solution is 1:3.5, heat to 90°C and react for 12 hours, filter the obtained product to obtain a filter residue, wash and dry the filter residue, and then sinter at 800°C for 7 hours to obtain nano-thermal radiation particles with a germanium shell fully covered with a tourmaline structure.

[0053] S2, taking nano thermal radiation particles and placing them in an organic solvent, adding a dispersant, and obtaining a thermal radiation slurry by stirring and dispersing, taking the thermal radiation slurry and mixing it evenly with polyamide fiber slices, drying and melt granulating to obtain thermal radiation masterbatch, taking the thermal radiation masterbatch for melt spinning, the melt spinning temperature is 260°C, the speed is 1100m / min, the spinneret hole diameter is 0.35mm, and then thermal stretching, relaxation and heat setting are performed to obtain thermal radiation fibers, the stretching ratio during stretching is 3.3, and the temperature during relaxation and heat setting is 70°C; finally, the thermal radiation fibers are woven to obtain a thermal radiation fiber layer; wherein the mass ratio of the nano thermal radiation particles, the organic solvent and the dispersant is 1:2:0.08, the mass ratio of the thermal radiation slurry to the polyamide fiber slices is 1:5, and the organic solvent is ethylene glycol, and the dispersant is sebacic acid.

[0054] S3. Nano thermal insulation particles are taken as online added components, polyester melt is used as the main melt, the mass ratio of nano thermal insulation particles to polyester melt is 12%, and the spinneret hole is set as a hollow structure, and online melt spinning is performed. The melt spinning temperature is 290°C, the speed is 1200m / min, the cross-section of the spinneret hole is annular, and the outer diameter is 0.6mm, and the inner diameter is 0.4mm. Then, hollow polyester fibers are obtained by heat stretching and relaxation heat setting. The stretching ratio during stretching is 3.2, and the temperature during relaxation heat setting is 90°C; finally, the hollow polyester fibers are woven to obtain a thermal insulation fiber layer.

[0055] S4, bonding the heat radiation fiber layer and the thermal insulation fiber layer to obtain the nano heat radiation warmth-keeping composite fabric.

[0056] Comparative Example 2

[0057] A nano thermal radiation warmth-keeping composite fabric, the composite fabric comprising a thermal radiation fiber layer as an inner layer material and a thermal insulation fiber layer as a surface layer material, wherein the textile raw material of the thermal radiation fiber layer is polyamide fiber filled with nano thermal radiation particles, and the nano thermal radiation particles are obtained by mixing nano germanium powder and nano tourmaline powder, and the textile raw material of the thermal insulation fiber layer is hollow polyester fiber filled with nano thermal insulation particles, and the nano thermal insulation particles are nano silica aerogel particles.

[0058] The preparation steps of the composite fabric are as follows:

[0059] S1, take nano-germanium powder and nano-tourmaline powder in a mass ratio of 1:9.3 (this mass ratio is the mass ratio of germanium shell to tourmaline of the nano-thermal radiation particles with a semi-covered tourmaline structure of germanium shell prepared in step S1 of Example 2. After testing, the density of the nano-thermal radiation particles with a semi-covered tourmaline structure of germanium shell prepared in Example 2 is 3.281g / cm 3 , while the density of germanium is 5.35g / cm 3 , the density of tourmaline is 3.15g / cm 3 , therefore the mass ratio calculated according to the density measurement method is 1:9.3) and directly mixed to obtain nano thermal radiation particles.

[0060] S2, taking nano thermal radiation particles and placing them in an organic solvent, adding a dispersant, and obtaining a thermal radiation slurry by stirring and dispersing, taking the thermal radiation slurry and mixing it evenly with polyamide fiber slices, drying and melt granulating to obtain thermal radiation masterbatch, taking the thermal radiation masterbatch for melt spinning, the melt spinning temperature is 260°C, the speed is 1100m / min, the spinneret hole diameter is 0.35mm, and then thermal stretching, relaxation and heat setting are performed to obtain thermal radiation fibers, the stretching ratio during stretching is 3.3, and the temperature during relaxation and heat setting is 70°C; finally, the thermal radiation fibers are woven to obtain a thermal radiation fiber layer; wherein the mass ratio of the nano thermal radiation particles, the organic solvent and the dispersant is 1:2:0.08, the mass ratio of the thermal radiation slurry to the polyamide fiber slices is 1:5, and the organic solvent is ethylene glycol, and the dispersant is sebacic acid.

[0061] S3. Nano thermal insulation particles are taken as online added components, polyester melt is used as the main melt, the mass ratio of nano thermal insulation particles to polyester melt is 12%, and the spinneret hole is set as a hollow structure, and online melt spinning is performed. The melt spinning temperature is 290°C, the speed is 1200m / min, the cross-section of the spinneret hole is annular, and the outer diameter is 0.6mm, and the inner diameter is 0.4mm. Then, hollow polyester fibers are obtained by heat stretching and relaxation heat setting. The stretching ratio during stretching is 3.2, and the temperature during relaxation heat setting is 90°C; finally, the hollow polyester fibers are woven to obtain a thermal insulation fiber layer.

[0062] S4, bonding the heat radiation fiber layer and the thermal insulation fiber layer to obtain the nano heat radiation warmth-keeping composite fabric.

[0063] 3. Performance Test

[0064] The composite fabrics prepared in Examples 1-3 and Comparative Examples 1-2 were cut to obtain samples of 10 cm×10 cm, and the far-infrared emissivity and far-infrared radiation temperature rise of each sample were tested according to the national standard GB-T 30127-2013 "Testing and evaluating the far-infrared performance of textiles"; in addition, the flat plate constant temperature difference heat dissipation method in the national standard GB / T 11048-1989 "Testing method for thermal insulation performance of textiles" was used to test the Crowe value of each sample. The test results are statistically obtained in the following Table 1:

[0065] Table 1: Far infrared emissivity and far infrared radiation temperature rise test results

[0066]

[0067]

[0068] As can be seen from Table 1 above, the far-infrared performance of the composite fabrics prepared by Examples 1-3 of the present invention is outstanding, especially Example 2, the far-infrared emissivity reaches 94.0%, and the temperature rise reaches 4.9°C. However, since Comparative Example 1 does not perform the dry etching step, and uses nano thermal radiation particles with a germanium shell fully coated tourmaline structure, its far-infrared emissivity is reduced to 89.9%, and the temperature rise is reduced to 2.8°C. Since Comparative Example 2 uses nano thermal radiation particles directly mixed with nano germanium powder and nano tourmaline powder, its far-infrared emissivity is only 88.6%, and the temperature rise is only 2.2°C. This shows that the use of germanium shell semi-coated tourmaline structure as nano thermal radiation particles can make the overall far-infrared performance of the fabric higher than that of ordinary directly mixed nano thermal radiation particles. In addition, the thermal insulation performance of Examples 1-3 is also better than that of Comparative Examples 1 and 2.

[0069] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A nano thermal radiation warming composite fabric, characterized in that: The composite fabric includes a heat radiation fiber layer as an inner layer material and a heat insulation fiber layer as a surface layer material, wherein the textile raw material of the heat radiation fiber layer is a matrix fiber filled with nano heat radiation particles, and the nano heat radiation particles adopt a germanium shell semi-covered tourmaline structure, and the textile raw material of the heat insulation fiber layer is a hollow polyester fiber filled with nano heat insulation particles.

2. The nano thermal radiation warming composite fabric according to claim 1, characterized in that: The matrix fiber is selected from one of polyester fiber, polyamide fiber, acrylic fiber, polypropylene fiber or spandex fiber.

3. The nano thermal radiation warming composite fabric according to claim 1, characterized in that: The nano thermal insulation particles are nano silicon dioxide aerogel particles or nano polyurethane aerogel particles.

4. A method for preparing a composite fabric with nano thermal radiation and warmth preservation as claimed in any one of claims 1 to 3, characterized in that the steps include: S1. Using nano-germanium dioxide powder and nano-tourmaline powder as raw materials, preparing nano-thermal radiation particles with a germanium shell and a semi-covered tourmaline structure; S2, placing nano thermal radiation particles in an organic solvent, adding a dispersant, stirring and dispersing to obtain a thermal radiation slurry, mixing the thermal radiation slurry with matrix fiber slices, drying and melt granulating to obtain a thermal radiation masterbatch, melt spinning the thermal radiation masterbatch, and then thermally stretching, relaxing and heat-setting to obtain a thermal radiation fiber, and finally spinning the thermal radiation fiber to obtain a thermal radiation fiber layer; S3, taking nano thermal insulation particles as an online added component, taking polyester melt as the main melt, and setting the spinneret hole as a hollow structure, performing online addition melt spinning, and then obtaining hollow polyester fibers through heat stretching, relaxation and heat setting, and finally weaving the hollow polyester fibers to obtain a thermal insulation fiber layer; S4, bonding the heat radiation fiber layer and the thermal insulation fiber layer to obtain the nano heat radiation warmth-keeping composite fabric.

5. The method for preparing the nano thermal radiation warm-keeping composite fabric according to claim 4, characterized in that: The specific process of step S1 is as follows: dissolving nano-germanium dioxide powder in a sodium hydroxide solution and adjusting the pH of the solution to 6-8 to obtain solution A; dispersing nano-tourmaline powder in a polyvinyl pyrrolidone solution and stirring for 6-12 hours to obtain solution B; mixing solution A and solution B evenly, adding a sodium borohydride solution to the mixed solution, heating to 80-100° C. and reacting for 10-14 hours; filtering the obtained product to obtain a filter residue; washing and drying the filter residue, and then sintering at 750-850° C. for 6-8 hours to obtain nano-thermal radiation particles with a tourmaline structure fully covered by a germanium shell; taking the nano-thermal radiation particles, removing part of the germanium shell on the surface of the particles by dry etching technology, and obtaining nano-thermal radiation particles with a tourmaline structure half covered by a germanium shell.

6. The method for preparing the nano thermal radiation warm-keeping composite fabric according to claim 5, characterized in that: The concentration of the sodium hydroxide solution is 10-14 mol / L, and the dosage ratio of the nano-germanium dioxide powder to the sodium hydroxide solution is 1 g:50-100 mL, the concentration of the polyvinyl pyrrolidone solution is 0.02-0.05 mg / mL, and the dosage ratio of the nano-tourmaline powder to the polyvinyl pyrrolidone solution is 1 g:20-50 mL, the mass ratio of the solution A to the solution B is 1:4-6, the concentration of the sodium borohydride solution is 0.1-0.3 g / mL, and the mass ratio of the sodium borohydride solution to the mixed solution is 1:3-4.

7. The method for preparing the nano thermal radiation warm-keeping composite fabric according to claim 5, characterized in that: The etching gases used in the dry etching are chlorine and oxygen, wherein the chlorine flow rate is 100-200sccm, the oxygen flow rate is 5-50sccm, the etching pressure is 50-200mtorr, the source power is 600-700W, the bias power is 120-150W, and the etching time is 3-5min.

8. The method for preparing the nano thermal radiation warm-keeping composite fabric according to claim 4, characterized in that: In step S2, the mass ratio of the nano thermal radiation particles, the organic solvent and the dispersant is 1:1.5-3:0.05-0.1, the mass ratio of the thermal radiation slurry to the matrix fiber slice is 1:3-8, and the organic solvent is one of ethanol, ethylene glycol or isopropanol, and the dispersant is one of polyvinyl pyrrolidone, sebacic acid, trimethylolethane, polyethylene glycol ester or phenyl benzoate.

9. The method for preparing the nano thermal radiation warm-keeping composite fabric according to claim 4, characterized in that: In step S2, the melt spinning temperature is 250-280°C, the speed is 800-1500 m / min, the spinneret diameter is 0.25-0.4 mm, the stretching ratio during stretching is 3.2-3.5, and the temperature during relaxation heat setting is 65-80°C.

10. The method for preparing the nano thermal radiation warm-keeping composite fabric according to claim 4, characterized in that: In step S3, the mass ratio of nano thermal insulation particles to polyester melt is 8-15%, the melt spinning temperature is 280-300°C, the speed is 1000-1400m / min, the spinneret cross-section is annular, and the outer diameter is 0.6mm, the inner diameter is 0.4mm, the stretching ratio during stretching is 3.0-3.4, and the temperature during relaxation heat setting is 80-100°C.

Citation Information

Patent Citations

  • Method for preparing Ge material by adopting Ge acid radical ion water-solubility precursor

    CN102049529A

  • Preparation method of nano-scale germanium dioxide powder

    CN108046312A

  • Electromagnetic shielding radiation-proof household textile fabric

    CN109097855A

  • Anti-static far infrared polyester fiber

    CN109137111A

  • Modified PET polyester fiber, preparation method and polyester fabric

    CN110735198A